Gastric Cancer Caused by Adenoma: Predictive Factors Associated with Lesions Other Than the Expanded Indications - Park, Seong Hwan (Gut Liver, 2018)
BACKGROUND/AIMS: We aimed to investigate whether the current indications for curative endoscopic resection (ER) of gastric cancer (GC) can be applied to GC caused by adenoma. Additionally, we attempted to identify factors predictive of lesions subsequently found in addition to the expanded indications for ER. METHODS: We retrospectively analyzed 342 patients diagnosed with GC caused by adenoma who underwent ER at a single tertiary center between February 2011 and December 2014. The gross whole tumor size was measured using the endoscopically resected specimen. The microscopic whole tumor size was measured using mapping paper. The estimated cancer size was calculated using the microscopic whole tumor size and the square root of the carcinoma component. RESULTS: A gross whole tumor size ≥3 cm, carcinoma component ≥35%, and gross ulceration were predictive of lesions other than the expanded indications for ER. The overall rate of lymph node metastasis was 0.3% (1/327), which only occurred in one patient with a lesion other than the expanded indications (4.5%, 1/22). CONCLUSIONS: The current indications for curative ER in GC can be applied to GC caused by adenoma. In cases suspected of having lesions other than the expanded indications, patients should be cautiously selected for ER to reduce the risk of an inappropriate procedure.